MENGATASI EROSI DAN TANAH LONGSOR MELALUI KEGIATAN â€œTEBAR WANGIâ€ DI DUSUN JAGALAN - Amanda Elliora Arista; Ayu Andira; Jihan Rona Fauziyah Ahmad; Kalya Dinda Az-Zahra; Novita Anastasya Fitri; Kusuma, Heri Septya (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Soil erosion is one of the biggest enemies for farmers in Indonesia. The speed of erosion that cannot be matched by the soil formation that occurs can cause serious global problems such as the land crisis. Strengthening the soil is one option to prevent erosion, one method is through planting plants. A strategic study and design is needed to compile appropriate activities such as an effective planting system. Therefore, we are holding the â€œTebar Wangiâ€ activity, which is a series of vetiver planting activities to overcome erosion and landslides. Vetiver is a plant that is easy to maintain and very effective in controlling erosion and landslides. Vetiver plants planted on hard, rocky slopes will hold soil particles tightly. The â€œTebar Wangiâ€ program will be carried out in collaboration with the Pemuda Harapan Sapta (PHS) Youth Organization which is expected to also increase the productivity of the PHS Youth Organization.